The prevalence of anemia and the factors associated with its severity among children aged 6-59 months in Ghana: A multi-level ordinal logistic regression. - Yordanos Sisay Asgedom; Aklilu Habte; Beshada Zerfu Woldegeorgis; Mengistu Meske Koyira; Beimnet Desalegn Kedida; Bezawit Melak Fente; Amanuel Yosef Gebrekidan; Gizachew Ambaw Kassie (PLoS ONE)
Introduction Anemia is a significant health problem that has a profound impact on young children under the age of five. It can result in severe consequences, such as stunted growth, impaired cognitive and motor development, increased illness, and even death. In Ghana, anemia is the leading cause of child mortality, yet there is a lack of information available on the prevalence of anemia and the factors associated with its severity in children under five in the country. To fill this gap, this study was conducted to investigate the prevalence and determinants of anemia severity among children aged 6-59 months in Ghana. Methods This study used data from the 2022 Ghana Demographic and Health Survey (GDHS) and included a weighted total sample of 3585 children aged 6-59 months. Given the hierarchical nature of the DHS data and the ordinal nature of anemia, a multilevel ordinal logistic regression model was employed. The Brant test was used to determine whether the proportional odds assumption was met (P ≥0.05). Deviance was used for model comparison. For the multivariable analysis, variables with a p-value ≤0.2 in the bi-variable analysis were considered. The Adjusted Odds Ratio (AOR) with a 95% Confidence Interval (CI) was reported as a factor associated with anemia severity in the multivariable multilevel proportional odds model. Results A study conducted in Ghanaian children aged 6-59 months found that 49.1% of them had anemia (95% CI: 47.4%-50.7%). The results indicated that 27.6% of patients had mild anemia, while 21.4% had moderate to severe anemia. Factors that were significantly associated with higher odds of childhood anemia included being 6-23 months old, male, having a maternal age of 15-24 or 25-34 years, belonging to poorer or wealthier households, having a higher birth order, being stunted, having maternal anemia, no media exposure, and living in the Northern, Upper East, or Upper West regions. Conclusion Anemia among children aged 6-59 months in Ghana is a major public health concern. It is recommended to improve access to the media, address maternal anemia through targeted interventions, and strengthen the wealth status of families. Furthermore, preconception care for mothers during pregnancy should be supported to reduce anemia in the long-term. Additionally, the early detection and management of stunted children should be strengthened to decrease childhood anemia.